Pengaruh Kualitas Produk, Persepsi Harga Dan Promosi Terhadap Keputusan Pembelian Di Shanii Konveksi - Felixia Budiarti Ramadhani; Dhian Tyas Untari; Andrian Andrian (Pusat Riset dan Inovasi Nasional, 2024)
This research aims to determine the influence of product quality, price perception and promotion on purchasing decisions at Shanii Konveksi. This type of research is quantitative. The population in this research are employees, business partners and people who use Shanii Konveksi services. The sampling technique uses the Saturated Sampling technique. The sample in this study consisted of 78 respondents (47 business partners, 31 people who used services). Data collection technique by distributing questionnaires via Google Form. Hypothesis testing in this research uses Multiple Linear Regression analysis. The research subjects are business partners and service users of Shanii Konveksi. The results of this research show that the variables of product quality, price perception and promotion partially and simultaneously have a significant effect and have a positive influence on the Purchasing Decision variable.